ANALYSIS OF HETEROGENEITIES IN THE UNIT COST OF UNIVERSITY EDUCATION IN NIGERIA - Iyiomo, Oyetakin Akinrotimi; Olayiwola, Adeosun (European Scientific Journal, ESJ, 2014)
This study analyzed the heterogeneities in the unit cost of university education in Nigeria. As a descriptive research design, it made use of 2,300 undergraduates who cut across eight faculties in each of the six sampled universities through stratified random sampling techniques. Three research questions were raised and analyzed in the study. Data were collected through the use of self developed instruments titled, University Education Social Unit Cost Questionnaire (UESUCQ) this instrument was meant to collect secondary data on sources universities funds and expenditure and valid from the appropriated and audited accounts of the universities. The second instrument is named University Education Private Unit Cost Questionnaire. (UEPUCQ) used for collecting primary data from the students concerned validated and with reliability coefficient of r = 0.92.Data were analyzed through descriptive statistics tools. The study found that from 2007 to 2012, followed the same trend with that of the crude cost with the highest S U C of N3,816,191.23 from Obafemi Awolowo University (male) and N3,817,803.19 (female). The average reveals that the males took the highest social cost of N5,253,835,276 and S U C of N1,629,780.60 as against N1,624,483.76 by the female. Also, average Social Unit Cost across faculties reveal that Faculty of Medicine had the highest (N2,589,335.30) followed by Engineering with N2,589,114.40. But the least Social Unit Cost was recorded in the faculty of Law (N2,431,694.41). A cursorily look at the findings of the study reveals that both Private Unit Cost and Social Unit Cost of undergraduate vary from one university to the other, whether State or Federal and among disciplines. It also varies among gender. In the area of wastages, difference also existed between Federal and State Universities in terms of cost. On direct Social Unit Cost, a significant difference existed between the adjusted direct Social Unit Cost among State and Federal universities in South –West Nigeria from 2007 to 2012. The result provides enough evidence for recommendation that there is a need for educating more Female students as the Social Unit Cost was high in most of the universities sampled. Also, there should be an assessment of the cost-benefit analysis of university undergraduate education and thus encourage government at both state and federal to divert the hard-earned resources on fields/courses that are of greater benefits to both individuals and the society at large.